2021
DOI: 10.30574/ijsra.2021.3.2.0131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of Neutrophil Lymphocyte Ratio (NLR) as a marker of Spontaneous Bacterial Peritonitis (SBP) in patients with cirrhosis-An exploratory study

Abstract: Background and objective: The diagnosis of spontaneous bacterial peritonitis (SBP) is made by presence of ≥250 polymorphonuclear neutrophil (PMN)/mm3 in the ascitic fluid. Paracentesis despite being the gold standard has its inherent risks and complications. Blood neutrophil-lymphocyte ratio is a simple test for inflammation. Highly sensitive C reactive protein (hsCRP) is a marker of inflammation which is mainly synthesized by the liver. We aimed to evaluate clinical utility of NLR and hsCRP as less invasive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…The results were nearly agreed with the study of Baweja et al (13) who found no significant difference in age between infected and uninfected people. These findings disprove the hypothesis that socioeconomic status is a major confounding factor.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results were nearly agreed with the study of Baweja et al (13) who found no significant difference in age between infected and uninfected people. These findings disprove the hypothesis that socioeconomic status is a major confounding factor.…”
Section: Discussionsupporting
confidence: 91%
“…Another study done by Baweja and his colleagues (13) found that blood NLR >3.38 was shown to be a cutoff value for identifying SBP in patients with ascites, with a sensitivity of 94% and a specificity of 80% among those with the condition. Similarly, highsensitivity C-reactive protein (hsCRP) was elevated compared to normal in both cases and controls, although patients with and without SBP/CNNA did not differ significantly from one another statistically (p value=0.194).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation